Attitudes of Turkish anatomists toward cadaver donation - SARIKAYA, ÖZLEM; ŞEHİRLİ, ÜMİT SÜLEYMAN (WILEY-LISS, 2004)
There is an insufficient number of cadavers in anatomy education in Turkey. This is because of decreased number of unclaimed bodies and very few cadaver donations. Increasing the number of cadaver donation is one of the probable solutions. Although anatomists encourage people to donate bodies, the attitudes of anatomists toward donating their own bodies for dissection is not well known. In this study, the attitudes of Turkish anatomists toward cadaver donation were evaluated. The questionnaires were sent to the anatomists in Turkey by mail and E-mail. Eighty-three anatomists replied to the questionnaire. The main solutions proposed for cadaver insufficiency included increasing the supply of unclaimed bodies (77.1%) and increasing body donation (78.3%). Further, 51.8% of the respondents thought that increasing body donation was a long-term solution. The general belief (83.1%) was that a campaign would help to increase body donation and 47% of respondents were willing to participate in such a campaign. Of the 83 anatomists, 20.5% of the respondents donated their organs and 49.4% were planning to donate them. Further, 15.7% were planning to donate their bodies; however, 63.9% did not consider donating. The main reasons of the respondents to object the donation were: to be dissected by a colleague (75.7%), the unacceptability of donation by family (26.5%), psychological reasons (43.4%), the anxiety of disrespectful behavior to cadavers (26.5%), and religious beliefs (3.6%). Although the majority of the respondents objected to donating their bodies due to psychological reasons, body donation was proposed as the main solution of cadaver insufficiency. (C) 2004 Wiley-Liss, Inc.
Keywords: cadaver donation; donation; anatomist; anatomy education; bequest; ORGAN DONATION; BODY DONATION; MEDICAL-STUDENTS; PUBLIC-ATTITUDES; GROSS-ANATOMY; TRANSPLANTATION; ETHICS; RELIGION; RESPECT; PROGRAM